Perceptions of plain packaging and health warnings among university students in Turkey: a survey-based experiment - Asena Caner; Belgi Turan; Mehmet Y. Gürdal; Sibel Güven (BMC, 2023)
Abstract Background Cigarette pack design plays a crucial role in attracting customers, especially when other marketing methods are limited by policy. University students who engage in casual smoking take the risk of developing an addiction. The objective of this study was to assess the effects of plain packaging (PP) and graphic health warnings (GHWs) on cigarette packages on three outcome variables (negative affect, avoidant responses, and intentions to quit) among ever-smoker university students in Ankara, Turkey, where youth smoking prevalence is high. Methods An online survey-based experiment was used to collect data. The respondents were randomly assigned to one of the five conditions that contained images of cigarette packs with specific design elements. Regression analyses (n = 623) were used to compare across conditions and to estimate the effects of combined warnings (versus text-only warnings), stronger GHWs (versus old GHWs), and PP (versus branded packages) on the outcome variables, accounting for potential confounders. Results Stronger GHWs generated more negative affect (0.31 points out of 5, p = 0.010) and avoidant responses (0.42 points out of 5, p = 0.002) than old warnings (when brand logos were visible). Plain packages generated more negative affect (0.48 points out of 5, p < 0.001) and avoidant responses (0.46 points out of 5, p = 0.001) than branded packages (with old warnings). Disentangling the effects of PP and new GHWs revealed that neither had individual differential effect on intentions to quit within 6 months. Conclusions Although no differential effect of PP or harsher GHWs was found on intentions to quit when respondents were exposed to images on screen, both design elements were found to be effective in generating negative affect and avoidant responses. More work is needed to design effective tobacco control measures among youth during critical years of tertiary education.